Value relevance of balanced scorecard:Malaysian evidence / Mohd Halim Kadri - Kadri, Mohd Halim (Institute of Graduate Studies, UiTM, 2012)
This thesis is aimed at investigating the value relevance of Balanced Scorecard (BSC) measures incremental to book value and earnings of Malaysian public listed firms. The objectives of the thesis are to investigate (a) whether book value and earnings are still value relevance; (b) whether BSC measures are value relevance; (c) whether firm specific characteristics influence the value relevance of BSC measures; (d) whether book value and earnings could predict future market price; and (e) whether BSC measures could predict future market price. The sample was selected from Malaysian firms that have been listed for more than 10 years. Using a six year data from 2003 – 2008, the sample size is 1899 firm-years for the analysis current year market price and 1467 firm-years for the analysis of future year market price.